Employers’ perspectives on Malaysian graduates’ skills: A contemporary study - Abdul Wahab, Nurul Asmida; Saleh, Hasan (Penerbit UTHM, 2025)
This study aims to determine the perspectives of Malaysian employers on the importance of employability skills falling short among engineers, education system at Higher Education Institutions (HEIs), and important graduates’ attributes. From this study, a contemporary study was developed and has been designed to serve as a reference by the time of this study was carried out. This contemporary study was developed based on the employers’ perspectives (dependent variable), skills falling short, HEIs’ education system, and graduates’ attributes (independent variables). It is aimed that this proposed contemporary study will be used as an insightful reference for present and upcoming researchers undergoing similar studies.